PECULIARITIES OF UKRAINE'S FOREIGN ECONOMIC ACTIVITY IN THE FACE OF GLOBAL CHALLENGES - NEMCHENKO, Valerii; SKLIAR, Larysa; MAKSYMENKO, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the key features and challenges facing Ukraine’s foreign economic activity (FEA) in the context of global instability and full-scale military aggression by the Russian Federation. The authors conducted a comprehensive analysis of the current state of Ukrainian foreign trade, using SWOT analysis as the primary tool to identify internal strengths and weaknesses and external opportunities and threats. An analysis of statistical data for 2019–2024 reveals the devastating impact of the war on FEA: a sharp decline in exports, especially in the metallurgical sector, and a significant increase in the negative trade balance. The export structure demonstrated a critical dependence on the agro-industrial complex (grains, oils), while the share of products with high added value, particularly mechanical engineering, decreased. The import structure indicates an acute need for fuel, machinery, equipment, and goods necessary for defense and reconstruction. Within the SWOT analysis framework, it was determined that the strengths of Ukraine are its advantageous geographical location, powerful agricultural potential, and qualified workforce. At the same time, the weaknesses remain a high level of corruption, political instability, underdeveloped infrastructure, and dependence on raw materials for exports. The key opportunities are deepening integration with the EU, growing global demand for food, and attracting investments for post-war reconstruction. The main threats are recognized as ongoing military aggression, increased worldwide protectionism, and competition in world markets. It also emphasized the need to develop a comprehensive state strategy to overcome internal weaknesses, diversify exports towards goods with higher added value, modernize infrastructure and maximize the benefits of the European integration course to ensure sustainable economic development.
Keywords: foreign economic activity; SWOT analysis; international trade; investments; economic development; Ukraine